2021
DOI: 10.3390/jcdd8090109
|View full text |Cite
|
Sign up to set email alerts
|

Left Ventricular Myocardial Noncompaction with Advanced Atrioventricular Conduction Disorder and Ventricular Arrhythmias in a Young Patient: Role of MIB1 Gene

Abstract: Left ventricular noncompaction (LVNC) is a structural abnormality of the left ventricle, usually described as an isolated condition, or sometimes associated with other structural cardiac diseases. LVNC is generally asymptomatic, although it may present conduction disorders, arrhythmias, and heart failure. Here, we present the case of a patient who came to our attention with a severe LVNC phenotype associated with advanced AV conduction disorder, and supraventricular and ventricular arrhythmias at young age, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Although these issues did not show a significant relationship with P and VUS genetic mutations, probably due to the small sample size, their importance in long-term outcome and risk stratification was described previously ( 11 , 12 , 14 , 19 , 27 , 28 , 31 , 32 ). Syncope was reported as an early warning sign of ventricular arrhythmias; moreover, some studies revealed the importance of the P genotype in the development of different types of ventricular and supraventricular arrhythmias ( 12 14 , 18 , 22 , 31 , 42 ). It was also suggested that repolarization abnormalities indicated by inverted T waves and LBBB also have connections with cardiovascular events ( 12 , 43 45 ).…”
Section: Discussionmentioning
confidence: 99%
“…Although these issues did not show a significant relationship with P and VUS genetic mutations, probably due to the small sample size, their importance in long-term outcome and risk stratification was described previously ( 11 , 12 , 14 , 19 , 27 , 28 , 31 , 32 ). Syncope was reported as an early warning sign of ventricular arrhythmias; moreover, some studies revealed the importance of the P genotype in the development of different types of ventricular and supraventricular arrhythmias ( 12 14 , 18 , 22 , 31 , 42 ). It was also suggested that repolarization abnormalities indicated by inverted T waves and LBBB also have connections with cardiovascular events ( 12 , 43 45 ).…”
Section: Discussionmentioning
confidence: 99%
“…Variants in MIB1 are associated with LVNC, but patient s31, carrying the variant MIB1 :c.376C>T, displayed a typical LV form of ACM, with extensive fibro-adipose substitution LV free wall and enlarged LV without trabeculation [ 41 , 42 ].…”
Section: Discussionmentioning
confidence: 99%